Politeness Strategies Analysis in "Two Distant Strangers" - Damara, Gabriella Sella; Romala, Almira Ghassani Shabrina (Lingual Journal of Language and Culture; Vol 14 No 2 (2022): Lingual: Journal of Language and Culture, 2022)
The effort to satisfy someone else’s face wants is referred to as a politeness strategy in linguistics. These strategies are used in everyday communication. Aside from using politeness strategies in daily life dialogues, politeness strategies can also be seen in films. The object of this study is the script of a short film on Netflix entitled Two Distant Strangers. There are three key characters which are Carter, Merk, and Perri.  This research aims to discover the types of politeness strategies utilized by the characters in Two Distant Strangers and the sociological factors that influence the usage of politeness strategies in the short film. This research employs the pragmatic approach and qualitative methodology. From the analysis, the researchers found that all characters in Two Distant Strangers implemented four types of politeness strategies. The researchers also discovered that the characters’ utterances demonstrated a relationship between politeness strategies and related sociological factors. Bald on-record is the most frequently used strategy because Merk, the character who acts as a police officer, believes he is more powerful than the other characters. The sociological factor of high to low power plays a part in why Merk is not hesitant to ignore other characters’ faces and command them as he likes.